St. Lucia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2003 Article IV Consultation highlights that after a contraction in GDP of more than 4 percent in 2001 and only a marginal expansion in 2002, the pace of economic growth in St. Lucia accelerated in 2003 to 3.7 percent, driven by a rebound in tourism of close to 17 percent. Despite the pickup in growth, the overall economic situation remained difficult in 2003, as an ongoing recovery in the tourism sector has not spilled over to the whole economy. Unemployment remained high, and bank credit to the private sector is declining.